Enhancing Consumer Revisit Intentions: A Comprehensive Study on the Impact of Store Atmosphere, Experential Marketing, and Brand Associations at Praya Social Hub Bali Cafe - Mawaddah, Nurifina; Kusuma, I Gusti Agung Eka Teja; Anggraini, Ni Putu Nita (Journal of International Conference Proceedings, 2023)
This research aims to explore the impact of store atmosphere, experiential marketing, and brand associations on consumer revisit intention at Praya Social Hub Bali café. The study was conducted at Praya Social Hub Bali, with the population consisting of all customers who have visited and made purchases at the cafe. The sample size of 100 respondents was determined using non-probability purposive sampling. Data collected through questionnaire distribution were deemed suitable for analysis, with subsequent testing and analysis conducted using multiple linear regression. The findings indicate that store atmosphere, experiential marketing, and brand associations positively influence revisit intention at Praya Social Hub Bali. This implies that an improvement in store atmosphere, experiential marketing, and brand associations leads to higher consumer revisit intention. Brand associations emerge as the most dominant variable in influencing consumer revisit intention, attributed to its ability to create emotional connections, reinforce quality perceptions, and establish unique appeal distinguishing it from competitors. The implications of this research suggest the need to enhance store atmosphere, experiential marketing strategies, and brand associations to elevate consumer return visits to Praya Social Hub Bali.